1991
DOI: 10.1093/infdis/163.2.305
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Incidence of Clinical and Asymptomatic Lyme Borreliosis in a Population at Risk

Abstract: A past history of clinical Lyme borreliosis and the 6-month incidence of clinical and asymptomatic Lyme borreliosis was studied prospectively in a high-risk population. In the spring, blood samples were drawn from 950 Swiss orienteers, who also answered a questionnaire. IgG antiBorrelia burgdorferi antibodies were detected by ELISA. Positive IgG antibodies were seen in 248 (26.1%), in contrast to 3.9%-6.0% in two groups of controls (n = 101). Of the orienteers, 1.9%-3.1% had a past history of definite or proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
10

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(74 citation statements)
references
References 28 publications
4
60
0
10
Order By: Relevance
“…These results must be confirmed by culture of B. vafaisiana from human tissue. If B. valaisiana is rather common and infectious, but exerts a low pathogenic potential, this species might well contribute to the frequent finding of asymptomatic seropositivity among residents in Switzerland (10) and The Netherlands (42), two countries where B. vafaisiana is known to occur in ticks (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…These results must be confirmed by culture of B. vafaisiana from human tissue. If B. valaisiana is rather common and infectious, but exerts a low pathogenic potential, this species might well contribute to the frequent finding of asymptomatic seropositivity among residents in Switzerland (10) and The Netherlands (42), two countries where B. vafaisiana is known to occur in ticks (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Woodmice (Apodemus sylvaticus L.) and yellow-necked mice (Apodemus flavicolus Melchior) are the principal reservoirs of B. burgdorferi (Humair et al 1993). The incidence of Lyme borreliosis is 1.8 cases per 100,000 inhabitants (Chamot 1989, Fahrer et al 1990, Zhioua 1993.…”
Section: Methodsmentioning
confidence: 99%
“…In an LD vaccine trial in the United States, 30 (11%) of the 269 study participants who acquired LD had asymptomatic IgG seroconversion to B. burgdorferi (196). Several seroprevalence studies in Europe have demonstrated that Ͼ50% of B. burgdorferiseropositive persons do not recall having any symptoms of LD (64,74,139). Furthermore, levels of IgM and IgG antibodies to B. burgdorferi decline slowly after treatment, and these antibodies have been demonstrated to persist for months to years after clinical cure (65,94).…”
Section: Clinical Manifestationsmentioning
confidence: 99%